Rancang Bangun dan Alat Bantu Pengepres Kulit Untuk Alat Musik Khas Riau (Kompang) - Novison, Roni; Amnur Akhyan; Agus Wijianto (Politeknik Caltex Riau, 2023)
One of the traditional musical instruments originating from Riau Province which is made of wood and leather is the kompang. The process of making kompang is still done conventionally so that the time needed in the process of making Kompang is getting longer. Because of that, a tool for pressing Kompang skin was designed using the pulling method using 12 hooks. In the withdrawal process using the pressure generated from the hydraulic jack which has a load of 5 Tons. After carrying out several comparative tests between kompang produced by UMKM and produced with the Kompang skin pressing tool, we obtained data such as processing time and sound intensity on Kompang. The conventional process of making Kompang obtained data for processing time of 141.8 minutes while using a leather press tool is 28.4 minutes. The time difference between the conventional manufacturing process and the manufacturing process using a Kompang skin pressing tool is 113.4 minutes faster. The next data obtained is that the average sound intensity in conventionally produced Kompang (MSMEs) is 93.9 dB. At the Kompang sound intensity produced with the Kompang skin pressing tool is 105.8 dB. It can be concluded that the sound intensity obtained in Kompang which is produced with the Kompang skin pressing tool is higher than Kompang which is produced using conventional methods. Keywords: Kompang, UMKM, Press tools